PENGEMBANGAN KOMPETENSI GURU DALAM MENERAPKAN PROGRAM PENDIDIKAN INDIVIDUAL DI SEKOLAH INKLUSIF LABSCHOOL UNESA - Ashar, S.Pd., M.Ed., Muhammad Nurul; Budiyanto, Budiyanto; Sujarwanto, Sujarwanto; Nur, Devina Rahmadiani Kamaruddin; Minarsih, Ni Made Marlin; Vrisaba, Nanda Audia (Universitas Negeri Surabaya, 2025)
Teachers in inclusive education units do not sufficiently possess the competencies to provide learning services for students with special needs. Therefore, short courses for teachers in inclusive education schools are highly necessary, particularly at Labschool UNESA. Special education teachers at Labschool UNESA lack adequate knowledge and skills in implementing individual education programs for students with special needs. Thus, specialized training is required, focusing on the topic of individual education programs, particularly in the areas of identification and assessment. The training was conducted in person through lectures, Q&A sessions, and case studies. The training proceeded smoothly, attended by forty teachers over two phases. The results of the training indicate an increase in teacher competence, marked by improved final test scores compared to initial test results. Furthermore, the satisfaction evaluation regarding the materials and facilitators also revealed a high level of satisfaction among participants. These results indicate that the training process went as planned. Further training is needed to enhance the competencies that the teachers have already acquired. Keywords: Teacher Competency, Individual Education Plan, Inclusive Schools